Effects of L-Threonine and L-Tryptophan Supplementation on Growth Performance of Native Chickens during the Grower Phase - Lisnahan , Charles V.; Nahak, Oktovianus R. (International Journal of Poultry Science, 2019)
Objective: This study was conducted to determine the effect of L-threonine and L-tryptophan feed supplementation on body weight gain, feed intake, feed conversion, carcass percentage and abdominal fat of native chickens during the grower phase. Materials and Methods: A total of 112 six-week-old native chickens were randomly divided into 4 treatments and 4 replications, with 7 birds in each replicate. The dietary treatments were: T0 (control feed without L-tryptophan and L-threonine supplementation); T1 (supplementation with 0.07% L-tryptophan and 0.25% L-threonine), T2 (0.14% L-tryptophan and 0.58% L-threonine) and T3 (0.20% L-tryptophan and 0.85% L-threonine). Feed intake, body weight gain, feed conversion ratio, carcass percentage and abdominal fat were measured and the data were analyzed using one-way analysis of variance. Differences between treatments were examined using Duncan’s test. Results: Body weight gain, feed intake, carcass percentage were increased with increasing amounts of L-threonine and L-tryptophan (p